2017
DOI: 10.2503/hortj.okd-049
|View full text |Cite
|
Sign up to set email alerts
|

Highly Efficient Agroinoculation Method for Tomato Plants with <i>Tomato Yellow Leaf Curl Kanchanaburi Virus</i>

Abstract: Tomato yellow leaf curl disease caused by begomoviruses is a serious threat to tomato (Solanum lycopersicum L.) production. If begomoviruses, transmitted by whitefly (Bemisia tabaci), infect tomato plants during early growth, production can be almost entirely lost. Tomato yellow leaf curl Kanchanaburi virus (TYLCKaV), a bipartite Begomovirus, is emerging as an important threat to solanaceous crop production in Southeast Asia. The lack of mechanical transmission of some begomoviruses is a major experimental con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 29 publications
1
19
0
Order By: Relevance
“…These results showed that both components are necessary for symptom expression in N. benthamiana. Infection of N. benthamiana with bipartite begmovirus DNA A of TYLCKaV alone did not produce symptoms as also observed in our previous study (Koeda et al, 2017). Our study demonstrated that constructed clones had infectivity, and agroinoculation of PepYLCIV DNA A and DNA B can successfully induce virus symptoms.…”
Section: Inoculation Of N Benthamiana and Tomatoes With Pepylcivsupporting
confidence: 61%
See 4 more Smart Citations
“…These results showed that both components are necessary for symptom expression in N. benthamiana. Infection of N. benthamiana with bipartite begmovirus DNA A of TYLCKaV alone did not produce symptoms as also observed in our previous study (Koeda et al, 2017). Our study demonstrated that constructed clones had infectivity, and agroinoculation of PepYLCIV DNA A and DNA B can successfully induce virus symptoms.…”
Section: Inoculation Of N Benthamiana and Tomatoes With Pepylcivsupporting
confidence: 61%
“…In pepper-cultivating fields in Indonesia, mixed infection with PepYLCIV, TYLCKaV, and AYVV is frequently observed (Koeda et al, 2016). In our previous study, we successfully inoculated tomatoes with TYLCKaV by agroinoculation (Koeda et al, 2017). However, we did not succeed in the agroinoculation of peppers with TYLCKaV (data not shown).…”
Section: Inoculation Of Peppers With Pepylciv By Graftingmentioning
confidence: 99%
See 3 more Smart Citations